Concurrent agreement and test-retest reliability of a global-positioning-system device for measuring maximal horizontal deceleration ability in elite youth academy soccer players - Jones, L. H.; Leduc, C.; Greatorex, K.; Callaghan, S. J.; Weaving, D.; Harper, D. J.; Bliss, A. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Investigate the concurrent agreement and test-retest reliability of 10-Hz global-positioning-system (GPS) device against a criterion measure (47-Hz radar device) to assess maximal horizontal deceleration ability (maximum deceleration [DECMax], average deceleration [DECAve], time to stop, and distance to stop).